IMF Staff papers : Volume 15 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1968)
An earlier version of this paper was presented to a conference on the topic 'Is the Business Cycle Obsolete?' organized by the Social Science Research Council and held in London, England, on April 3-7, 1967.